'The knowledgeable marketing practitioner': practice and professional knowing in marketing work. Issue 13 (2nd September 2018) - Gross, Nicole; Laamanen, Mikko
ABSTRACT: This paper examines the knowledge constructs that professionals draw upon when engaging in marketing work. Our conceptual approach stems from a critical analysis of marketing work foregrounding the practitioners' professional knowledge and practice of marketing work. We identify 13 pertinent knowledge constructs–some of which are illustrated by vignettes–showcasing the shared and multifaceted nature of professional knowledge in a small- and medium-sized enterprise. By exploring how practitioners deploy their knowledge of marketing in practice, we conclude what the marketing discipline can learn from professional knowing. We contribute to the marketing work literature by considering the ontological role of professional knowing in dereifying marketing work from textbook knowledge along with its implications for the critical understanding of the perceived gap between marketing theorising and practice.